Generación de valor en la oficina farmacéutica privada en el Perú - Juárez, José R. (2019)
Objective: To establish which are the processes that generate value for the patient / user in the Pharmaceutical Office. Material and methods: the literature review and critical reading of the theory of value generation for the patient / user was carried out; as well as the application of these concepts to the generation of professional value of the Pharmaceutical Chemist and the identification of the processes that generate value in the Pharmacy Office. Results: The processes that generate value at the level of activities that the Chemist Pharmacist as Technical Director performs or supervises were identified, and he is responsible in the pharmacy office. These activities have been grouped into: Activities oriented to the Product, the Patient and the Community and, that each one of them is related to the fulfillment of the Good Practices of Storage, Dispensation, Pharmacotherapeutic Follow-up, Pharmacovigilance and Good Practices of Pharmacy. Conclusions: the identification of the processes and their activities, which generate medical care value in the Pharmacy Office, are strategic activities and should be developed with priority. The processes that generate sanitary value in the Pharmacy Office occur in three levels: those oriented to the product, oriented to the patient and oriented to the community, and are the responsibility of the Technical Director of the establishment, based on compliance with Good Practices.